The discovery learning and Google sites: Its application in learning the process of urine formation for high school students - Mustofa, Ali; Hayuana, Wachidah; Damopolii, Insar; Ibrohim, Ibrohim; Susilo, Herawati (Inornatus: Biology Education Journal, 2024)
In the application of discovery learning in the classroom, the main source of science information is not the teacher, but various other sources that can be easily accessed by students. Learning sources that can be flexibly accessed by students are Google sites. This study was conducted to analyze how the implementation of discovery learning and Google sites in learning the formation of human urine. The research was conducted in one of the high schools in Malang. The students involved were grade XI. Data were collected through observation, teacher reflection sheets, learning implementation sheets (student and teacher activities), and student response questionnaires. The research data were narrated based on observations and learning implementation and student responses were calculated using percentages. The research findings show that the implementation of discovery learning and Google sites in learning the formation of human urine has changed the learning conditions of students for the better. High school students can actively answer teacher questions, are able to work on student worksheets, can work together well, discuss actively and draw conclusions. Google sites are a medium that can help students to find information related to the learning being carried out. Student responses related to learning scored 78.95 which is included in the good category. Collaborative activities among students can run well. Students agree that they do not forget the responsibilities given by their group to each individual.